ANALISIS FAKTOR KUALITAS PELAYANAN DALAM MENINGKATKAN KEPUASAN PELANGGAN PADA PT UNIBLESS INDO MULTI JAKARTA SELATAN - Agustina, Teni; Oktiani, Nurvi; Lestari, Nurlaela Eva Puji (2021)
For attempting the Quality of Service as a one of marketing strategy, it is an obligation for fulfill all of Customer Expectation, The Company must have bargained service which can be received and felt by consumer, and it is good choices, that the service can be excess than the expectation of consumer, until it can be created the high of Service Quality performance. In other hand the purpose of this research know the factors from service quality which have been done and which is the others factor must be given more attention for increasing the consumer service. The methods from this research use quantitative, with data have been collected by Questionnaires, the amount of samples consist of 60 respondents, from the Customer of PT UNIBLESS INDO MUKTI, beside that use analysis Factor with the Processing data use Correlation factor, extraction factor and Rotation Factor From the result of research, it can be decided the factor that have been done in this company is the knowledge of customer needs, and in other hands the factors which must have been more attention is how to the company create the high value and product performance, in advice from the result the company must think of the steps or strategies for creating the high value until the purpose of company for increasing customer satisfaction have achieved